(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
EcG instruments measure the electrical activity of the heart muscle to determine the state of the heart. The quality of the ECG signal is a key factor in the detection of heart disease. This work will take a 12-channel EKG of the AD8232 single-channel portable EKG device. This one-channel EKG device with a 12-channel EKG collection technique makes it possible to diagnose the ECG much more conveniently.